Spatial distribution, homologue patterns and ecological risks of chlorinated paraffins in mangrove sediments along the South China Coast. (1st February 2022) - Chen, Hui; Han, Xu; Liang, Bowen; Deng, Man; Du, Bibai; Zeng, Lixi
Abstract: The spatial distribution, homologue patterns, and ecological risks of chlorinated paraffins (CPs) were investigated in sediments from sixteen mangrove wetlands along the South China Coast (SCS). The total concentrations of CPs in mangrove sediments from Guangdong, Fujian, Guangxi, and Hainan were in the range of 933–4760, 619–2300, 375–1550, and 271–658 ng/g dry weight, respectively. The contamination levels and spatial distribution of short-chain and medium-chain CPs (SCCPs and MCCPs, respectively) in mangrove sediments were mainly affected by local population scale and CP industries. The dominant CP patterns in sediments were C10 –11 Cl6-8 and C14 Cl7-9 for SCCPs and MCCPs, respectively. Redundancy analysis, based on CP levels and several potential influencing factors showed that MCCPs/SCCPs ratio was the main factor affecting the accumulation of CPs in mangrove sediments. Additionally, MCCP concentrations were significantly correlated with total organic carbon (TOC), indicating that TOC might affect MCCP accumulation in mangrove sediments. Risk assessments indicated that CPs would pose medium ecological risks to sediment dwelling organisms in nearly one-third of the sampling sites. This is the first comprehensive report of the sedimentary SCCPs and MCCPs in mangrove wetlands along the SCS and highlights the need for more sediment toxicity data for CPs. Graphical abstract: Image 1 Highlights: Sedimentary CPs in mangrove wetlands along coastal area of China was first reported. C10-11 SCCPs and C14 MCCPs were the dominant homologues in mangrove sediments. MCCPs/SCCPs ratio was the main factor affecting the accumulation of CPs. TOC might affect MCCP accumulation in mangrove sediment.